Numerical simulation and performance improvement for a small size shell-and-tube heat exchanger with trefoil-hole baffles. (5th October 2015) - You, Yonghua; Chen, Yuqi; Xie, Mengqian; Luo, Xiaobing; Jiao, Lan; Huang, Suyi
Abstract: The shellside turbulent heat transfer enhancement with trefoil-hole baffles was validated in our previous experimental investigation on a small size heat exchanger. In the present work, the commercial software ANSYS FLUENT is adopted to conduct the numerical study on the thermal augmentation of trefoil-hole baffles. Structural modification is made on the small size heat exchanger for better thermo-hydraulic performances, and the effects of baffle distance are investigated. Computation results demonstrate that the current numerical model, where the whole heat exchanger, including tubes, baffles and fluids on both shell and tube sides, etc., is modeled, could predict the thermo-hydraulic performances considerably well by comparing with experimental data. Moreover, it is found that with the structural modification, the pressure loss on the shellside of the small size heat exchanger decreases by ∼21.0%, and the shellside overall thermo-hydraulic performance rises by ∼21.9%. In addition, the convection heat transfer coefficient on the shellside is observed to decrease monotonically with the decrement of baffle number (from 7795.4 to 6431.2 W/m 2 K at shellside Re = 11, 350), while the variation tendency of shellside overall thermo-hydraulic performance with baffle number is on the opposite, with the value between 558.3 and 712.1 W/(m 2 K kPa) at shellside Re = 11, 350. Highlights: The whole heat exchanger is computed for thermal augmentation of trefoil-hole baffle. The present model has a reasonable precision by comparing with experimental data. Shellside overall performance rises by ∼22% with the structural modification. The effects of baffle distance on thermo-hydraulic performances are studied.